Communicating health and illness - Gwyn, Richard, 1956- (SAGE, 2002)
This accessible book provides a cogent review of the literature on discourse analysis as it pertains to medical and health matters. It demonstrates the centrality of discourse analysis to an understanding of health and communication. Introducing original research from his own studies, Richard Gwyn focuses on language and communication issues.